Faktor-Faktor Yang Berhubungan Dengan Kepatuhan Penggunaan APD Pada Pekerja Di PLTU Nii Tanasa Kendari, Kabupaten Konawe Sulawesi Tenggara Tahun 2023 - Alma Putri Indar Sari; Yusuf Sabilu; Syawal K. Saptaputra (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Enforcing the use of PPE serves as a preventive measure against workplace accidents, particularly within the Nii Tanasa Kendari PLTU vicinity. Adherence to PPE reflects a behavior influenced by consciousness and environmental elements. The aim of this study was to establish connections between knowledge, attitudes, actions, PPE availability, and familial backing concerning PPE compliance among Nii Tanasa Kendari PLTU workers in Konawe Regency, Southeast Sulawesi in 2023. Employing a quantitative approach, this research adopted a cross-sectional design and was executed at PLTU Nii Tanasa Kendari in Konawe Regency during November 2023. Sampling involved 149 individuals through proportional random sampling, followed by data analysis via the chi-square test. Findings revealed correlations between knowledge and PPE compliance (0.035 < 0.05), attitudes and PPE compliance (0.027 < 0.05), actions and PPE compliance (0.021 < 0.05), PPE availability and PPE compliance (0.035 < 0.05), as well as family support and PPE compliance (0.021 < 0.05).